2012
DOI: 10.1002/mus.23427
|View full text |Cite
|
Sign up to set email alerts
|

Spastic cocontraction in hemiparesis: Effects of botulinum toxin

Abstract: In spastic hemiparesis, stretch may facilitate agonist recruitment and spastic cocontraction. In the non-injected antagonist, cocontraction may be reduced by enhanced reciprocal inhibition from a more relaxed, and therefore stretched, agonist, or through decreased recurrent inhibition from the injected muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Accordingly, spastic co-contraction of non-injected antagonistic muscle is reduced after BoNT-A at elbow level in stroke patients. This has been attributed to possible reinforcement of reciprocal inhibition through a decreased recurrent inhibition from the injected muscles (Gracies et al 2009; Vinti et al 2012). BoNT-A did not modify the excitability of reciprocal group Ia interneurons in an animal preparation, but the excitability of Renshaw cells was also not modified (Hagenah et al 1977).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, spastic co-contraction of non-injected antagonistic muscle is reduced after BoNT-A at elbow level in stroke patients. This has been attributed to possible reinforcement of reciprocal inhibition through a decreased recurrent inhibition from the injected muscles (Gracies et al 2009; Vinti et al 2012). BoNT-A did not modify the excitability of reciprocal group Ia interneurons in an animal preparation, but the excitability of Renshaw cells was also not modified (Hagenah et al 1977).…”
Section: Discussionmentioning
confidence: 99%
“…However, because their spinal excitability did not change after muscular injection in forearm muscles, it has been claimed that BoNT-A clinical effect is only limited to its peripheral action in stroke patients (Girlanda et al 1997). However, it has been shown in arm muscles that BoNT-A reduces spastic co-contraction of non-injected antagonistic muscles (Gracies et al 2009; Vinti et al 2012). Moreover, we have recently shown in stroke patients that BoNT-A reduces recurrent inhibition of lumbar motoneurons (Marchand-Pauvert et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 The toxin, produced by Clostridium botulinum, contains proteins that block transmission of acetylcholine across the neuromuscular junction by interfering with presynaptic neurotransmitter unloading mechanisms. With regards to children with BPBP and nonspastic contractures, BTX-A has been shown to enhance the ability of muscle to passively stretch 30 and magnify active motion through inhibition of imbalanced antagonistic muscles. 31,32 Some authors believe BTX-A has the additional ability to alter cortical patterning.…”
Section: Discussionmentioning
confidence: 98%
“…BoNT injected in upper limb muscles reduces muscle tone, with perceived functional benefits [ 109 ]. Some studies have also shown that BoNT treatment is effective in decreasing cocontraction of antagonist muscles, facilitating agonist recruitment and increasing active range of motion [ 111 ]. However, improvements in active upper limb function remain to be demonstrated [ 110 ].…”
Section: Robotic Systems Combined With Other Therapeutic Innovatiomentioning
confidence: 99%